Enhanced solubility of novel poly(benzoxazole)s with a soft linkage and a rigid pendant group. Issue 5 (14th September 2012) - Fu, Qian; Zhuang, Qixin; Liu, Xiaoyun; Han, Zhewen
Abstract Aromatic poly(benzoxazole)s are a class of rigid‐rod conjugated polymers. However, their poor solubility in organic solvents limits potential applications. Thus, a good method that can address this dilemma is needed, given that existing methods involve models with either poor solubility but good thermal stability or good solubility but poor thermal stability. In this paper we report a novel aromatic poly(benzoxazole) with a soft linkage and a rigid pendant group. Structural characterizations of the polymers via Fourier transform infrared and proton nuclear magnetic resonance spectroscopy reveal the formation of a benzoxazole ring and an imide ring. The introduction of rigid pendant groups improved the solubility and enhanced the thermal stability of the polymer, which was impaired by the incorporation of the soft linkage. Most of these polymers are soluble at room temperature or when heated in dimethyl sulfoxide, N, N‐dimethylformamide or N, N‐dimethylacetamide. Some polymers can even be dissolved in m‐cresol and tetrahydrofuran. A 10% weight loss in these polymers was observed at temperatures over 410 °C. Moreover, the incorporation of the imide pendant group increased the conjugation length of the polymer structural unit and accelerated electron delocalization. Copyright © 2012 Society of Chemical Industry